Fabrication of Ketoprofen Controlled-release Tablets using Biopolymeric Hydrophilic Matrices: In-Vitro Studies: Ketoprofen CR Tablets by Biopolymers - Rashid, Sheikh A.; Khan, Gul M.; Haider, Husnain; Khan, Barkat A. (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2017)
: Ketoprofen is propionic acid derivative and belongs to the Non-Steroidal anti-inflammatory group of drugs. Due to the short half-life, dosage frequency, patient non-compliance and side effects such as gastrointestinal disturbance, peptic ulceration and gastro intestinal bleeding, it is considered to be good candidate for formulation into controlled release dosage forms. Directly compressed controlled released (CR) tablets using Acrylic acid derivatives were prepared and evaluated. In-Vitro Physicochemical assessment of the formulated tablets were performed using different physicochemical, dimensional and quality control tests such as weight variation, thickness and diameter, hardness test, friability test, content uniformity, disintegration and dissolution testing. Results of all these tests were formed within acceptable range. The effect of carbomer polymers on the tablet characteristics, drug release rates, release patterns and release kinetics were investigated. The F2-metric technique was applied to compare dissolution profiles of ketoprofen and carbopol tablets with ketoprofen SR-tablets taken as standard preparation. Acrylic acid derivatives when used as polymers resulted in an extended release profile of about 12 h. Using Higuchi’s model and the Korsmeyer equation, the drug release mechanism from the tablets was found to be an anomalous type involving diffusion and erosion. Controlled-release Ketoprofen tablets appear to be a good choice for the symptomatic treatment of rheumatoid arthritis and osteoarthritis. Convenient once-daily administration may help improve patients' compliance.